What are the barriers to physical activity in patients with chronic plaque psoriasis?. (13th April 2020) - Auker, L.; Cordingley, L.; Pye, S.R.; Griffiths, C.E.M.; Young, H.S.
Summary: Background: Psoriasis is associated with an increased risk of cardiovascular disease. Despite recommendation that exercise is important for cardiorespiratory fitness, patients with psoriasis avoid participation in physical activities for reasons that are, as yet, unclear. Objectives: This study investigated the relationship between psoriasis‐specific experiences and self‐reported patterns of exercise, hypothesizing that individuals with psoriasis are less likely to engage in physical activity for reasons that are related to their psoriasis. Methods: In total 404 patients with chronic plaque psoriasis were recruited. History, examination and physical activity were assessed for each participant. Results: Overall, 52·8% ( n = 188) of patients with psoriasis aged 18–65 years and 66% ( n = 37) of those aged > 65 years engaged in less than the recommended amount of physical activity for cardiorespiratory fitness. As the severity and psychosocial impact of psoriasis increased, the participation in exercise (of all intensities) decreased. There was a significant negative correlation between Psoriasis Area and Severity Index and total activity in women aged 18–65 years ( r = −0·19, 95% confidence interval −0·36 to 0; P = 0·04) and a significant negative correlation between physical activity and Dermatology Life Quality Index (DLQI) in all participants ( r = −0·11, 95% confidence interval −0·21 to 0; P = 0·04). Individual components of the DLQI identified barriers to physical activity including skin sensitivity and reluctance to participate in leisure activities. Conclusions: Psoriasis‐specific factors – severity, skin sensitivity, clothing choice, participation in social/leisure activities, and treatments – contribute to exercise avoidance and may augment the increased risk of cardiovascular disease in patients with psoriasis. Abstract : What is already known about this topic? Psoriasis is associated with an increased prevalence of risk factors for cardiovascular disease. Despite recommendation that exercise is important for cardiorespiratory fitness, patients with moderate‐to-severe psoriasis participate in very little physical exercise for reasons that are, as yet, unclear. What does this study add? This study quantifies the significant lack of engagement with exercise in the population of people with psoriasis. Physical activity in those with psoriasis is significantly influenced by psoriasis severity, quality of life and a number of previously unrecognized psoriasis‐specific barriers. What is the translational message? Supporting patients with psoriasis to undertake regular physical activity could directly benefit weight management, cardiovascular disease and risk of metabolic syndrome, and increase wellbeing and psychosocial functioning. Linked Comment: Jarrett. Br J Dermatol 2020; 183 :988–989 . Plain language summary available online